Kadar Protein Dan Sifat Organoleptik Bakso Goreng "Basreng" Ikan Lele (Clarias batrachus) Dengan Penambahan Tepung Ubi Jalar Oranye (Ipomoea batatas L) Dan Tepung Tapioka - WIJAYANTI, DEBBY; , Dra. Suparti, M.Si (2016)
Fried meatballs is one processed meat products and has a high nutritional value because it is rich in animal protein. In this study, fried meatballs using basic ingredients of catfish. Catfish caontains water, protein, fat, minerals, calcium and vitamin A. To make the fried meatballs necessary fillers or thickeners such as orange sweet potato flour and tapioca flour. This study aims to determine the protein content and organoleptic qualities meatballs fried catfish with the addition of orange sweet potato flour and tapioca flour. The method used in this study is an experimental method by using a Completely Randomized Design of the factorial. These factors are the concentration of orange sweet potato flour (30 grams, 20 grams, 10 grams) and tapioca flour (40 grams, 60 grams, 80 grams) with 9 treatment level 2 replications. Descriptive data analysis of quantitative protein assays. Results of research on the highest protein content T3U1 (orange sweet potato flour 10 grams + tapioca flour 40 grams) worth of 1,88% and lowest in T2U2 (orange sweet potato flour 20 grams + tapioca flour 60 grams) worth of 1,00%. Best organoleptic results in treatment T3U1 with characteristic dark brown color, savory taste-not bitter, distinctive aroma of meat, crispy texture-not greasy and acceptance of people like. The results showed that the lower the concentration of orange sweet potato flour and tapioca flour, the higher the protein content of the fried meatballs.